DOI: 10.1007/3-540-39118-5_12
|View full text |Cite
|
Sign up to set email alerts
|

On Privacy Homomorphisms (Extended Abstract)

Abstract: An additive privacy homomorphism is an encryption function in which the decryption of a sum (or possibly some other operation) of ciphers is the s u m of the corresponding messages. Rivest, Adleman, and Dertouzos have proposed four different additive privacy homomorphisms. In this paper, we show that two of them are insecure under a ciphertext only attack and the other two can be broken by a known plaintext attack. We also introduce the notion of an R -additive privacy homomorphism, which is essentially an add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 8 publications
0
37
0
Order By: Relevance
“…However, this encryption suffers from known-plaintext attacks [4], which means p and q could be found if a pair of cleartext and ciphertext is known to an adversary.…”
Section: A Adversary Modelmentioning
confidence: 99%
“…However, this encryption suffers from known-plaintext attacks [4], which means p and q could be found if a pair of cleartext and ciphertext is known to an adversary.…”
Section: A Adversary Modelmentioning
confidence: 99%
“…A privacy homomorphism [6] is an encryption function which allows the encrypted data to be operated on without the knowledge of the decryption function.…”
Section: B Homomorphic Encryptionmentioning
confidence: 99%
“…It was firstly considered by Rivest et al who suggested some homomorphic encryption schemes [1]. However, these schemes are insecure [4]. Later, the fully homomorphic encryption (FHE) schemes [5,6,7] are proposed.…”
Section: Introductionmentioning
confidence: 99%